Memória da prostituição: lembranças da "Casa da Antonieta" - Simili, Ivana Guilherme [UNESP] (My University, 1995)
O trabalho é uma reflexão sobre memória, feita através de lembranças de uma casa de prostituição, a da "Antonieta", que existiu em Assis entre 1940 e 1978. O objetivo foi revelar aspectos da história da prostituição, que foi marcada pela existência das casas de prostituição nas paisagens das cidades brasileiras, com vistas à compreensão da memória e do imaginário que se constituíram em tomo desses lugares, cujos reflexos estão na maneira como são lembrados e esquecidos

This dissertation is a case study, on memory, written through the remembrances of a "whore house", the Antonieta's that was located in the city of Assis, São Paulo state, from 1940 to 1978. Its purpose was to reveal scenes of a prostitution history, that was constructed by the presence of brothels in the scenery of the Brazilian cities. It intends a comprehension of the meemory and imegery that were built around these plesure houses, that still alive in the way that one remembers or forgets them.
Memory of prostitution: memories of "Casa da Antonieta"